Corrosion reaction of iron exposed to the open atmosphere in the Antarctic - Gancedo, J. R.; Marco, J.F.; Gracia, Mercedes; Joseph, G.; Núñez, R. A. (Springer, 1994)
Within a cooperative program for the elaboration of a Latin American Map of Atmospheric Corrosion, weathering steel and mild steel samples were exposed to the Antarctic atmosphere and the corrosion products analyzed by ICEMS, XPS and XRD. Superparamagnetic α-FeOOH was the main corrosion product after 24 h of exposure. Cl− ions are found on the surface of the corroded samples by XPS. Financial support from the Fundación Andes (project C-10810/2) and the Spanish CICYT (project 88NAO43) are gratefully acknowledged.